2020
DOI: 10.3390/su12219088
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Courier Services and Its Antecedents as a Determinant of Perceived Service Quality and Future Intention to Use Courier Service

Abstract: Service quality perceived by clients should be a crucial element in the process of co-creating sustainable services. This article aimed to examine relationships between five constructs: the usefulness of courier services, the ease of use of courier services, the trust in courier services, the service quality, and the future intention to use courier services. This research focuses on courier services. An electronic questionnaire was used to conduct confidential interviews. It was distributed between January and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 97 publications
(130 reference statements)
1
35
0
4
Order By: Relevance
“…Z. Rachmawati & Agus, 2020;Zhou, Zhang, & Ren, 2018). Moreover, together with these studies, several studies including (Chan, Ngai, & Moon, 2017;Ejdys & Gulc, 2020;M. Li et al, 2020;S.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Z. Rachmawati & Agus, 2020;Zhou, Zhang, & Ren, 2018). Moreover, together with these studies, several studies including (Chan, Ngai, & Moon, 2017;Ejdys & Gulc, 2020;M. Li et al, 2020;S.…”
Section: Discussionmentioning
confidence: 93%
“…The results of a study were found that the factors of system quality, information quality, and design quality that constitute the quality of business affect trust and satisfaction and affect transaction intention. Ejdys and Gulc (2020) stated that the more customers visit the website, the higher the likelihood of purchase on the website. Based on such prior research, the website quality factor, which is a logistical service factor before purchase, was redefined and a hypothesis was established about the relationship between trust and commitment.…”
mentioning
confidence: 99%
“…Moreover, the scientific research conducted so far was mainly concentrated on identifying criteria/ attributes/factors affecting the courier service quality and the methods of evaluating them, omitting the existing relationship between the factors. The research on the courier service quality considered only one perspective, usually clients of courier services (individuals or business customers) [31][32][33][34][35][39][40][41][42] omitting the perspective of the sender-an online shop and a courier company. Considering the conclusions of analysed research on service quality, the article aims to analyse courier service quality from a multi-shareholder perspective, as it allows to formulate comprehensive and novel conclusions towards future directions of service quality.…”
Section: Literature Review Concerning the Courier Service Qualitymentioning
confidence: 99%
“…The results confirmed statistically significant relationships between the variables or the ease of use and the trust in service, the usefulness and the trust in service, the trust in service and the service quality, and, finally, the service quality and the future intention to use the service. The developed scale to measure the usefulness, the ease of use and customer trust in the context of courier service research was the most crucial contribution to the methodology [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Service quality determines the advantages of a company from competitors [3]. Along with the development of e-commerce, there is increasingly fierce competition among logistics service providers [4]. Quality of logistics services is recognized as a significant business component, competitiveness, and overall customer satisfaction [5].…”
Section: Introductionmentioning
confidence: 99%